Cytotoxicity 2018
DOI: 10.5772/intechopen.78616
|View full text |Cite
|
Sign up to set email alerts
|

Review of In Vitro Toxicity of Nanoparticles and Nanorods—Part 2

Abstract: The specific use of engineered nanostructures in biomedical applications has become very attractive, due to their ability to interface and target specific cells and tissues to execute their functions. Additionally, there is continuous progress in research on new nanostructures with unique optical, magnetic, catalytic and electrochemical properties that can be exploited for therapeutic or diagnostic methods. On the other hand, as nanostructures become widely used in many different applications, the unspecific e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 144 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…Similar results on MWCNT-induced cytotoxicity have been shown also before, with concentrations ranging between 1 and 10 µg mL −1 on THP-1 and BEAS-2B cells. [20] We first focused on the possibility that CNM exposure would trigger patterns of cytokine secretion. For this, IL-1α, IL-1β, IL-4, IL-5, IL-6, IL-10, IL-17, IFNγ, and TNF were quantified in the cell culture supernatant after 48-h exposure.…”
Section: Macrophages Respond To Cnm Exposure By Secreting Distinct Sementioning
confidence: 99%
“…Similar results on MWCNT-induced cytotoxicity have been shown also before, with concentrations ranging between 1 and 10 µg mL −1 on THP-1 and BEAS-2B cells. [20] We first focused on the possibility that CNM exposure would trigger patterns of cytokine secretion. For this, IL-1α, IL-1β, IL-4, IL-5, IL-6, IL-10, IL-17, IFNγ, and TNF were quantified in the cell culture supernatant after 48-h exposure.…”
Section: Macrophages Respond To Cnm Exposure By Secreting Distinct Sementioning
confidence: 99%
“…1 Magnetic nanoparticles (NPs) are important nanomaterials, and due to their magnetic properties and biocompatibility, they have been widely used for cell separation, 2 cell guidance, 3 drug delivery, 4,5 and hyperthermia; 6,7 in biosensors; 8 and as contrast agents in magnetic resonance imaging (MRI). 9,10 Iron-based materials are preferred due to their ease of fabrication and coating, magnetic properties, 11 and ability to absorb an 808 nm laser and convert it into heat. 6 In addition, it is an approved material for clinical use by the Food and Drug Administration (FDA), 12 making it attractive for biological applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, the cytotoxicity of NiNPs might be linked to the dissolution and release of metallic ions, as it was suggested for other metallic nanoparticles, such as AgNPs [41], which may also explain the observed linear dose-response curve (Figure 1). For instance, a similar behaviour that was found for ZnO NPs was related to the cytosolic concentration of Zn 2+ as well as to an apoptotic death pathway [42]. At this stage of research, the cause of cell death remains unknown, although apoptosis was shown to be the underlying mechanism used by ZnO NPs to induce cell death.…”
Section: Physicochemical Form Of Ni In Cell Cytosolsmentioning
confidence: 59%